1999
DOI: 10.1136/adc.81.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural phenotype of Cornelia de Lange syndrome

Abstract: A postal questionnaire was used to study 49 individuals with Cornelia de Lange syndrome (including both the classical and the mild forms) to ascertain behavioural phenotype. Ages ranged from early childhood to adulthood (mean age, 10.2 years; SD, 7.8) and the degree of mental retardation from borderline (10%), through mild (8%), moderate (18%), and severe (20%) to profound (43%). A wide variety of symptoms occurred frequently, notably hyperactivity (40%), self injury (44%), daily aggression (49%), and sleep di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
125
3
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(152 citation statements)
references
References 21 publications
21
125
3
3
Order By: Relevance
“…CdLS is associated with intellectual disability ranging from mild to profound, health problems including vision and hearing impairments and gastro-oesophageal reflux (Berney, Ireland & Burn, 1999;Jackson et al, 1993;Collis et al, 2008;Hall, Arron, Sloneem and Oliver, 2008;. Behavioral problems associated with CdLS include impulsivity, repetitive and self injurious behaviors (Berney et al, 1999;Hyman, Oliver and Hall, 2002, Moss et al, In press). …”
Section: Introductionmentioning
confidence: 99%
“…CdLS is associated with intellectual disability ranging from mild to profound, health problems including vision and hearing impairments and gastro-oesophageal reflux (Berney, Ireland & Burn, 1999;Jackson et al, 1993;Collis et al, 2008;Hall, Arron, Sloneem and Oliver, 2008;. Behavioral problems associated with CdLS include impulsivity, repetitive and self injurious behaviors (Berney et al, 1999;Hyman, Oliver and Hall, 2002, Moss et al, In press). …”
Section: Introductionmentioning
confidence: 99%
“…Social Quotients indicated that 50% of participants had profound disabilities, 14% had severe, 17% moderate, 6% had mild intellectual disabilities and 14% of participants scored within the borderline or normal range. These figures are supported by a postal survey of 49 children and adults with CdLS with 43% of participants showing profound intellectual disabilities, 20% severe, 18% moderate, 8% mild and 10% borderline disabilities (Berney, Ireland, & Burn, 1999). Oliver et al (2008) using the Vineland Adaptive Behavior Scales report 50% of individuals with CdLS to have a profound intellectual disability this figure was 24, 15 and 11 for severe, moderate and mild respectively.…”
Section: Intellectual Disabilitymentioning
confidence: 81%
“…Gualtieri (1990) reported that the most common topographies of self-injury include biting (shown by 27% of individuals), hitting (20%), hair pulling (15%), head banging (11%) and picking (10%). Berney et al (1999) also found that finger biting and head banging was common in CdLS. In a recent case control study described higher levels of more mild forms of selfinjury.…”
Section: Self Injurious Behaviourmentioning
confidence: 86%
See 2 more Smart Citations